2016
DOI: 10.1051/radiopro/2016051
|View full text |Cite
|
Sign up to set email alerts
|

Integration of long-term radionuclide transport models MOIRA-LAKE and MOIRA-RIVER into Hydrological Dispersion Module of JRODOS

Abstract: -The integration of the lake and river MOIRA models into the JRODOS Hydrological Dispersion Module (HDM) modelling framework, that originally only predicted short-term radionuclide dispersion in river systems, was a key objective of the PREPARE project. Thanks to it, the capabilities of JRODOS-HDM have been increased with regard to modelling the long-term fate of radionuclides ( 137 Cs and 90 Sr) in freshwater systems and to predicting the radiation doses via aquatic exposure pathways, as well as the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…According this scenario the intensity of source of accidental release 137 Cs was defined by (Gallego et al, 2016) as shown in Figure 3a. The results of an ADM simulation for total (dry and wet) deposition on the surface of Mediterranean Sea were used as input data.…”
Section: Integration Of Threetox Model Into Jrodosmentioning
confidence: 99%
“…According this scenario the intensity of source of accidental release 137 Cs was defined by (Gallego et al, 2016) as shown in Figure 3a. The results of an ADM simulation for total (dry and wet) deposition on the surface of Mediterranean Sea were used as input data.…”
Section: Integration Of Threetox Model Into Jrodosmentioning
confidence: 99%
“…This process can be simulated only by 3D model. (Gallego et al, 2016) has been customized for the Niida River watershed. The watershed was divided into 20 strips.…”
Section: Contaminated Water Systems At Fukushima-daiichi Nppmentioning
confidence: 99%
“…As one of the tasks of the EC PREPARE project of the Hydrological Dispersion Module (HDM) of the decision support system -JRODOS (Zheleznyak et al, 2010(Zheleznyak et al, , 2016Gallego et al, 2016;Maderich et al, 2016) was planned to be implemented and tested for the simulation of the radionuclide transport in the water bodies of the region of Japan contaminated by the atmospheric fallout from the Fukushima-Daiichi Nuclear Power Plant (FDNPP).…”
Section: Introductionmentioning
confidence: 99%